Eco-Friendly Management of Pentalonia nigronervosa: The Vector of BBTV on Banana Crop - Baloch, Sabit Ali; Lanjar, Abdul Ghani; Syed, Tajwar Sultana; Khanzada, Muhammad Ali (Journal of Agriculture and Veterinary Science, 2025)
The Banana bunchy top virus (BBTV) is one of the most destructive viral diseases of banana worldwide, causing severe reductions in fruit yield and quality. Its vector, the banana aphid Pentalonia nigronervosa (Coquerel), is an efficient transmitter of BBTV and occurs wherever bananas are cultivated. This pest is regarded as one of the most serious and economically important insect pests of banana fields globally, including in Sindh Province, Pakistan. The present study was conducted to evaluate the effectiveness of various eco-friendly approaches for the management of P. nigronervosa under field conditions. Pheromone traps were installed at four different heights in banana plantations on the ground surface, 1, 2, and 3 meters (T₄), to determine the optimal placement for aphid monitoring. Aphid populations were recorded weekly for four weeks. A significant reduction (P < 0.05) in aphid density was observed in traps installed at 2 m height (T₃), which proved to be the most effective height for monitoring and suppressing P. nigronervosa populations compared with other levels. In a second field experiment, the insecticidal efficacy of four botanical extracts, neem oil (T₁), tobacco solution (T₂), neem leaf powder (T₃), and eucalyptus extract (T₄) was tested against an untreated control. Each extract was prepared separately and applied as a foliar spray. Aphid counts were taken one day before application and at 1, 3, and 6 days after treatment. Among the botanicals, the tobacco solution (T₂) caused the greatest reduction in aphid population (25.64 aphids per plant, P < 0.05), followed by neem oil (28.36), neem powder (30.39), and eucalyptus (30.39), compared with the control (45.67). The suppression achieved by the tobacco extract was significantly higher than that of eucalyptus but statistically similar to neem oil and neem powder. Overall, the findings suggest that pheromone traps installed at 2 m height and tobacco extract sprays are highly effective, eco-friendly tools for the management of P. nigronervosa in banana plantations, offering a sustainable alternative to conventional chemical insecticides.
Keywords: Banana; Aphid; Eco-friendly management